Strategic Direction of Public Policy in Scenario Planning for Sustainable Conservation of Lake Limboto - Djafar, Franky; Akibu, Rifka S. (Department of Public Administration, 2023)
Lake Limboto, classified among the 15 national priority lakes, is undergoing a critical condition and is predicted to transform into dry land by 2035 due to an annual decrease in area of 65.89 hectares. This situation demands strategic policies that have not been fully visible or effectively implemented, necessitating a more comprehensive approach and initiative. To address these challenges, scenario planning becomes crucial. The research method employed is qualitative, focusing on